(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Although of micrometric magnitude, the biological weapon used as an act of bioterrorism is a global danger. The possibility of using biological weapons, more and more as a security measure, is considered as a means of subversive activity rather than a means of open warfare. Contemporary bacteriology provides a higher level of techniques for creation of new deadly biological warfare agents. International bans on the production and use of bio agents are not sufficient guarantee and protection against the possible use of such agents in a future total war, nor are any obstacle for use in terrorist goals. Here, the question arises about the possibilities for achievement of total protection expressed through the forms of bio-defence and biosafety. In this paper, there is a systematic attempt made to examine the (un)reasonableness of the horrifying fear of modern genetic engineering technologies and the possibilities for production of new, more dangerous agents. The results of this paper point to relatively reassuring /complacent view in the biomedical community for the premature, but still realistic possibility of an apocalyptic scenario as a consequence of the use of bio agents. In addition to such views, scientific data on the relative efficacy of existing procedures for detection of agents and care of endangered/infected subjects on which antibiotic treatment, antibiotic-based therapies based on passive antibodies and prophylaxis measures will be used are also discussed.